Наукове забезпечення проблематики використання психіатричних знань під час розслідування злочинів проти життя і здоров’я особи - Хорошун, Д. В.; Khoroshun, D. V. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 4 (103). - С. 281-291, 2023)
На підставі аналізу юридичної літератури констатовано, що вчені всебічно досліджували окремі аспекти призначення судово-психіатричних і судовопсихологічних експертиз під час розслідування вбивств різних видів і тілесних ушкоджень, однак поза їхньою увагою залишалися особливості залучення спеціалістів до участі у слідчих (розшукових) діях. Наголошено, що ця проблематика, а також перспективи використання спеціальних знань згаданого виду в непроцесуальних формах потребують ґрунтовного аналізу та висвітлення в юридичній літературі задля вдосконалення практичної діяльності сторони обвинувачення у кримінальному провадженні.

The category of criminal offences against life and health is quite significant. A large number of crimes included in this category are characterised by a high level of social danger, as they encroach on the greatest social value which is life and health of a person. In the investigation of such crimes, it is typical to use specialised knowledge in the fields of forensic psychiatry and psychology in procedural and non-procedural forms. Given that the process of cognition and assimilation of scientific knowledge begins with clarification of the peculiarities of its historical development, the purpose of the article is to clarify the state of scientific development of the issues related to the use of special psychiatric and psychological knowledge in the investigation of crimes against life and health of a person. It has been determined that the current state of scientific significance of the use of special psychiatric and psychological knowledge in the investigation of crimes against human life and health is influenced by the peculiarities of development of criminal procedure legislation. In addition, based on the analysis of legal literature, the assessment of the developments made by Ukrainian scholars has been provided. It is established that careful attention has been paid to the study of certain aspects of the appointment of forensic psychiatric and forensic psychological examinations in the investigation of various types of murders, bodily injuries, and domestic violence. At the same time, based on the results of the generalisation of scientific works authored by Ukrainian scholars, it has been determined that the national legal literature does not address the peculiarities of involving specialists in investigative (search) actions in the course of investigation of crimes against life and health of a person, as well as the prospects for implementing non-procedural forms of using specialised knowledge. The article emphasizes that this issue, as well as the prospects for using specialised knowledge of psychology and psychiatry in non-procedural forms, require a thorough analysis and coverage in the legal literature in order to improve the practical activities of the prosecution in criminal proceedings.

На основании анализа юридической литературы констатировано, что ученые всесторонне исследовали отдельные аспекты назначения судебно-психиатрических и судебно-психологических экспертиз при расследовании убийств различных видов и телесных повреждений, однако без их внимания оставались особенности привлечения специалистов к участию в следственных (розыскных) действиях. Отмечено, что эта проблематика, а также перспективы использования специальных знаний данного вида в непроцессуальных формах требуют тщательного анализа и освещения в юридической литературе для совершенствования практической деятельности стороны обвинения в уголовном производстве.
Scientific support for the use of psychiatric knowledge in the investigation of crimes against human life and health
Keywords: кримінальне провадження; досудове розслідування; злочини проти життя і здоров’я; спеціальні знання; судова експертиза; судова психіатрія; психологічні знання; criminal proceedings; pre-trial investigation; crimes against life and health; special knowledge; forensic examination; forensic psychiatry; psychological knowledge; уголовное производство; досудебное расследование; преступления против жизни и здоровья; специальные знания; судебная экспертиза; судебная психиатрия; психологические знания